Sealing Occlusal Dentin Caries in Permanent Molars: 7-Year Results of a Randomized Controlled Trial. (January 2017) - Qvist, V.; Borum, M.K.; Møller, K.D.; Andersen, T.R.; Blanche, P.; Bakhshandeh, A.
The purpose of this study was to investigate the possibility of postponing restorative intervention of manifest occlusal caries in young, permanent dentition by non-invasive sealing. This RCT-designed study included 521 occlusal lesions in 521 patients aged 6 to 17 y. Based on clinical and radiographic assessments, all lesions required restorative treatment. After randomization (ratio 2:1), 368 resin sealings and 153 composite–resin restorations were performed by 68 dentists in 9 municipalities. The primary aims were to 1) analyze survival of sealings until replacement by restoration, 2) compare longevity of sealings and restorations until retreatments, and 3) compare effectiveness of sealings and restorations to halt caries progression in sealed lesions and beneath restorations. Furthermore, we aimed to identify factors influencing longevity and the effectiveness of sealings and restorations. Treatments were annually controlled, clinically and radiographically. After 7 y, the drop out rate was 8%, and 54% of the treatments were completed due to age. Of the sealings, 48% were retreated, including 31% replaced by restorations; 12% were still functioning. Of the restorations, 7% were repaired/renewed and 20% were still functioning. No endodontics was performed. Kaplan–Meier and Cox regression survival analyses were performed on 341 sealings and 152 restorations in first and second molar teeth. The 7-y survival was 37% (CI, 29% to 45%) for sealings and 91% (CI, 85% to 96%) for restorations (P < 0.001). The median survival time for sealings not replaced by restorations was 7.3 y (CI, 6.4 y to NA). Survival of sealings was increased in patients with low caries risk and/or excellent oral hygiene, second molars compared with first molars, and lesions not extending the middle one-third of the dentin. Survival of sealings was not influenced by municipality, sex, eruption stage or clinical surface cavitation. The results underline that it is possible to postpone or avoid restorative intervention of occlusal dentin caries lesions in young permanent teeth by non-invasive sealing. Knowledge Transfer Statement: The first restoration can ultimately be fatal for a young permanent tooth. A restoration may not be the final treatment but the start of an ongoing treatment with still more loss of tooth substance. The present study shows the possibility of treating occlusal dentin caries lesions with non-invasive resin sealings instead of conventional resin composite restorations in children and adolescents. Improved oral health can be expected.